(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article presents a qualitative and quantitative analysis of wastewater from silkworm enterprises, the pre- and post-chemical composition of wastewater generated during the extraction of silk fiber from cocoons, methods of complete analysis and chemical composition after analysis, as well as scientific justification for the possibility of reuse of treated wastewater in the process of extracting silk fiber from cocoons based on the results of the analysis. However, it has been shown that purified waters can also be used for greening the environment.